ANALISIS PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENILAIAN KINERJA MANAJER PADA PT. CIPTA BETON SINAR PERKASA DI MAKASSAR - Ibrahim H. Ahmad (AkMen JURNAL ILMIAH, 2014)
The purpose of this study was to determine the role of accounting as a performance assessment tool in PT. Cipta Perkasa Concrete beam in Makassar, as well as to obtain a clear picture of how the application of the accounting system at PT. Cipta Perkasa Concrete beam in Makassar. To achieve these objectives we used the technique of collecting data through observation, interview and documentation. The method of analysis used in this study is a descriptive analysis of the application of the accounting manager's performance appraisal. The results of the analysis conducted found that from the results of a comparative analysis between budget and actual cost of production which indicates that the difference in production costs incurred by the company in the production process is inefficient mix concrete and effective because the costs incurred by the company can not be used as a means of controlling production costs. While the results of the analysis of cost accounting, in particular the cost of production which indicates that the performance of each responsibility unit production costs in the PT. Cipta Perkasa Concrete beam in Makassar can be said to be effective because the cost of production of each of the cost is not in accordance with budgeted in the production process.